PENGELOLAAN TAMAN HUTAN RAYA SULTAN SYARIF HASYIM DI PROVINSI RIAU - Budiarto, Agung Syarif; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Forest is a natural resource potential and has a strategic role in development. The concept developed by the collaboration between central and local governments in forest management activities. Forest management concept is that through the FMU development. The development is expected to create better forest management by encouraging the achievement of forest conservation and welfare of the community, and can accommodate the demands and economic interests (PAD). The purpose of this study was to determine and analyze the implementation of the SSH Tahura management implemented by UPT KPHP Model Minas Tahura. In Riau Provincial Regulation No. 5 of 2015 on the Management of Forest Park Sultan Syarif Hasyim, Article 6 states Tahura SSH management includes planning, implementation, maintenance, utilization, development, security and protection. The place where you are investigating is UPT KPHP Minas Tahura Riau Province, with the consideration that the management of Forest Park Sultan Syarif Hasyim from the site level managed by UPT KPHP Minas Tahura. Who became informants in this study are those directly involved in the management of the Head of UPT KPHP Minas Tahura, Section Chief of Planning and use of forest areas, and the head of Rehabilitation and Forest Protection, Legal Bureau Riau Province. The results showed that the management of SSH Tahura through the process of planning, organizing, and monitoring. Implementation of the organizing function is still not optimal, this is because the funding for operational activities as well as still inadequate facilities and infrastructure to support the operation. The planning function is a function of local government management that significantly affect its implementation. This is because the functions of planning and mobilization UPT KPHP Model Minas Tahura in the region Tahura SSH is managing the potential environmental services and nature to be a source of input for PAD. PAD is still managed by the Forest Service. SSH Tahura management by UPT KPHP Model Minas Tahura supported by the Regulation No. 5 Year 2015 concerning the Management Tahura SSH. So, it is very reasonable when it is said in the results of this study Tahura management of SSH is still not optimal, because all management activities that have been planned at this time still ongoing.Keywords: Management, Forest Park Sultan Syarif Hasyim